Overcoming Bias and The Hurdles of the "Intention-Behaviour Gap" In Consumers Through Applied Innovation Management - Stephan HOOSE; Harald BEHRSCHMIDT; Bettina WEDIG-VÖSSING (Communications of International Proceedings, 2024)
Customer opinions and the actual behaviour of a customer sometimes differ diametrically. Management science refers to this as the intention-behaviour gap. When developing new products, it is important for manufacturers to obtain the customer's opinion on whether they would also demand the product. Using the canvas method, the customer's barriers, and perceptions of benefits in relation to the product can be identified and products can be further developed if necessary. Within a survey on newly developed pet food for dogs, this was tested with an added value for customers through climate-neutral production. In a first survey with n=1.119 customers, near 70% answered that they would buy such a product. The results of the second survey shown that only a significant minority of 65% (n=779) would be willing to pay more money for this product.
Keywords: customer behaviour; canvas; value proposition canvas; marketing; intention-behaviour gap